The review for the use of urban climatic map in the land use plan for urban planning - Ibrahim, Illyani; Abu Samah, Azizan; Fauzi, Rosmadi (Malaysian Institute of Planners, 2014)
Urbanization leads to positive and negative impacts on the society. While it accelerates economic growth, it also brings negative impact to the environment and people‘s health. The growth of urbanization is unavoidable; therefore, sustainability needs to be maintained to preserve the liveability of urban dwellers. The intention of this study is to review the use of climatic information in planning future developments in the local land use map. The studies of content and interview method were done in order to understand the real situation of this environmental mitigation. In further, the identification of the gaps of e study. The findings of this study were used to propose the climate indicators for the existing land use map. Future studies may focus on conducting preliminary experiments to apply the urban climatic map in the local context.